Decolonising the museum: the case of Zimbabwe Military Museum in Gweru - Chaterera, Forget; Nyawo, Vongai Z. (International Research Journals, 2016)
The Zimbabwe Military Museum in Gweru seems to be struggling to come out of the colonial shell in which it was established. The permanent collection on display represents the kind of legacy which elevates the white settler ideologies. Through objects on display, supported with English text panels, the Zimbabwe Military Museum documents and memorialises in a seemingly celebratory manner, the colonial dominance. The task of this paper is to advocate for a national museum that claims both the past and the present to construct a decolonised future for the local indigenous people. As public institutions whose purpose in life is to serve the public, museums in Zimbabwe need to seriously consider offering services that are meaningful and relevant to the local indigenous communities. For that noble obligation to be fulfilled, the local indigenous communities should be actively involved in museums’ programmes and activities. Using the qualitative and quantitative methodologies the paper examines the Zimbabwe Military Museum’s exhibitions, analysed the literature that goes with it and interviewed users and officials of the Zimbabwe Military Museum.